Sistem Informasi Berbasis Web Untuk Pemesanan Layanan Fotografi - Saadah, Rabiatus; Rezki, Muhammad; Ihsan, Muhammad Ifan Rifani (LPPM Universitas Bina Sarana Informatika, 2024)
Information systems are here to provide various supports and conveniences in various aspects of life, including in the economic sector. One example is a photo studio, which is a business in the economic sector that utilizes information systems. This business offers photography services with a wide target market. However, the process of promoting and managing photo studios is still mostly done manually and has not utilized the information system optimally, so it is prone to errors, such as in delivering service package information, ordering, and making reports. The use of information systems aims to minimize these errors while optimizing the promotion of services offered by service providers such as photo studios, photographers, and freelance videographers. This system is designed to display detailed information, including portfolios and galleries of work, making it easier for consumers to place orders. In addition, this information system can also generate periodic order reports for service providers. System development is carried out using the Waterfall method, PHP programming language, Laravel framework, and MySQL database.